Effect of Aqueous Enzymatic Extraction of Deer Oil on Its Components and Its Protective Effect on Gastric Mucosa Injury - Xia, Yun-Shi; Sun, Yin-shi; Liu, Chang; Li, Zhi-Man; Ren, Duo-Duo; Mu, Rui; Zhang, Yan-Ting; Bo, Pan-Pan; Zhao, Li-juan; Wang, Zi (Frontiers in Nutrition, 2021)
In this study, deer suet fat was used as a raw material to study the effects of aqueous enzymatic extraction of deer oil on its components, followed by studies into the potential protective activity and related molecular mechanisms of deer oil on ethanol-induced acute gastric mucosal injury in rats. The results show that aqueous enzymatic extraction of deer oil not only has a high extraction yield and has a small effect on the content of active ingredients. Deer oil can reduce total stomach injury. Without affecting the blood lipid level, it can reduce the oxidative stress, which is manifested by reducing the content of MPO and enhancing the activity level of SOD and GSH-Px. It also enhances the expression of defense factors E2, EGF and SS, it inhibits apoptosis evidenced by the enhanced of Bcl-2 and decreased expression of cleavage of caspase-3 and Bax. At the same time, it reduces inflammation, which is manifested by reducing the expression of IL-1β, IL-6 and TNF-α gastric tissue pro-inflammatory cytokines, and enhancing the expression of anti-inflammatory factors IL-4 and IL-10, and inhibiting the MAPK/NF-κB signaling pathway in gastric tissue.